Revolution with a human face: politics, culture, and community in Czechoslovakia, 1989 - 1992 - Krapfl, James (Cornell University Press, 2013)
The rhetoric of revolution -- The big bang of the signifiers -- The ideals of November -- The boundaries of community -- Power in the streets -- The will of the people